Practising human geography - Cloke, Paul J.; Sage eBooks (London : SAGE, 2004)
This work provides a critical introduction to recent disciplinary debates about the practice of human geography examining those methods and practices which are integral to doing geography.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human geography -- Methodology; Electronic books